Self-medication due to COVID-19 symptoms in rotating Nursing interns - Zuly Rivel Nazate-Chuga; Alexandra Roxana Rebolledo-Solis; Alexandra Patricia Abata-Erazo; Reudis Durán-Rodríguez (Revista Información Científica, 2023)
Introduction: self-medication can generate adverse reactions, drug interactions, delay and failure in the diagnosis of the disease, resistance to antibiotics and loss of health resources. During the COVID-19 pandemic, it is reported that the frequency of adverse reactions due to self-medication has doubled.